Crude Oil Price Fluctuation and Unemployment Nexus in Nigeria: Evidence from VECM Technique - Maijama’a, Rabiu; Musa, Kabiru Saidu (Energy Economics Letters, 2020)
The main objective of this paper is to examine the impact of crude oil fluctuation on the rate of unemployment in Nigeria using data for the period of 1991 to 2018 and employed VECM to realize the objective. The outcome from the VECM estimation revealed that population and economic growths were positive and significantly associated with unemployment while crude oil price and electricity consumption have significant negative sign with unemployment in the long-run but in the short-run only population growth was significant and positively signed with unemployment. From the granger causality, one-way causality runs from population growth to unemployment; economic growth to unemployment; crude oil price to unemployment; population growth to economic growth; crude oil price to population growth; crude oil price to economic growth; electricity consumption to economic growth. Variance decomposition indicate that population growth responded highly to shock in unemployment whereas impulse response function revealed that unemployment responded positively to shocks in economic growth and crude oil price while negatively to population growth and electricity consumption. Therefore, among the recommendations include population checking measures should be a long-term one, making strategies that provide and encourages greater continued economic growth, redirecting excess crude oil accounts earnings into areas of education, employment encouraging plans, improving healthcare services and infrastructure development plan. Lastly, supervising the activities of Power Holding Company of Nigeria (PHCN) in order to ensure constant supply of electricity to the industrial and domestic sectors would help in providing solution to the increasing rate of unemployment in Nigeria.